1991
DOI: 10.1007/bf00263832
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hemodonation in the corrective surgery of craniostenosis

Abstract: Homologous transfusions are mandatory in most surgical procedures for correcting craniofacial malformations in infancy. A program of preoperative and intraoperative auto-hemodonation was developed and carried out in eleven infants. Although homologous transfusion could have been avoided in only 7 patients, we think that further experiences and minor corrections of our program may improve these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…3 Erythrocyte transfusion is associated with many serious adverse events, including increased mortality in the pediatric surgical population. 5 Numerous techniques intended to reduce intraoperative blood loss during craniosynostosis surgery have been studied, including autologous blood predonation, 6 short-term normovolemic hemodilution, 7 and intraoperative blood salvage. 3,8 Most of these techniques reported disappointing results, with relatively low benefits in terms of transfusion requirements.…”
mentioning
confidence: 99%
“…3 Erythrocyte transfusion is associated with many serious adverse events, including increased mortality in the pediatric surgical population. 5 Numerous techniques intended to reduce intraoperative blood loss during craniosynostosis surgery have been studied, including autologous blood predonation, 6 short-term normovolemic hemodilution, 7 and intraoperative blood salvage. 3,8 Most of these techniques reported disappointing results, with relatively low benefits in terms of transfusion requirements.…”
mentioning
confidence: 99%
“…PAD in pediatric patients weighing 6.7 kg or more has been reported. 25,29 In fact, it has been performed in cardiac lesion patients as young as 3 years of age and weighing as little as 12.7 kg. 6 An average volume phlebotomized can range from 10 to 20% 29 of circulating blood volume or to a reported maximum of 19 mL/kg.…”
Section: Preoperative Autologous Donationmentioning
confidence: 99%
“…31 Light narcosis can be induced with oral midazolam administered 30 minutes prior to the procedure. 29 This strategy is efficacious for patients who have alloantibodies or rare blood types and for those who refuse homologous blood transfusion. The cost, timing and risk of donation, 32 patient size and circulating blood volume as well as the logistics of getting to and from the donation site are all factors that must be considered.…”
Section: Preoperative Autologous Donationmentioning
confidence: 99%
See 1 more Smart Citation
“…24,35 One study had a transfusion rate of 36% after ANH during craniosynostosis corrections. 21 One study found no reduction in transfusion rates or amounts with ANH. 15 Aly Hassan found that ANH was well tolerated in the pediatric population without measurable signs of anaerobic metabolism.…”
mentioning
confidence: 98%